Parent-Child Dynamics in Gibran’s “On Children”: A Philosophical and Literary Inquiry - Khadka, Ashish Bahadur (NPRC Journal of Multidisciplinary Research, 2025)
Background: Khalil Gibran’s seminal work, The Prophet (1923), presents a revolutionary philosophy on parenting in its chapter "On Children." It challenges deep-seated, traditional notions of children as parental property, advocating instead for a model of radical generational autonomy. This philosophy often conflicts with both collectivist cultural values, such as Confucian filial piety, and modern parenting trends like overinvolvement, making a systematic analysis of its tenets and contemporary relevance critically needed. Objective: This study aims to conduct a philosophical and literary inquiry into Gibran’s "On Children." It seeks to critically analyze its challenge to parental ownership, decode its central metaphors, and evaluate its applicability and tensions within modern parenting discourses across different cultural contexts. Methods: The research employs a qualitative design, utilizing a close textual analysis of the poem to identify and interpret its key philosophical arguments and symbolic language (e.g., "arrows," "bows," "yesterday"). Furthermore, the study uses a comparative theoretical analysis, framing Gibran’s ideas against John Bowlby’s (1969) Attachment Theory and contemporary parenting models (e.g., authoritative parenting, helicopter parenting) to bridge literary and psychological perspectives. Findings: The analysis reveals that Gibran’s work provides a profound critique of parental control, positing a balanced vision where parents act as stable supports ("bows") who must release children ("arrows") to their own destinies. Significant tension exists between this individualistic vision and collectivist parenting values. While prescient in warning against overparenting, Gibran’s philosophy potentially underestimates the value of intergenerational guidance and the complex psychological interdependence within families. Conclusion: "On Children" offers a transformative and enduring framework for parent-child relationships. Its core strength lies in redefining parental love from control to supportive guidance, advocating for children’s inherent independence. The study concludes that Gibran’s vision remains a vital, though provocative, resource for navigating the perennial challenge of balancing familial bonds with the nurturing of individual autonomy. Implementation: The insights from this study can be implemented in educational and clinical settings. Parenting workshops, family therapy practices, and educational curricula can use Gibran’s metaphors as a powerful tool to facilitate discussions on healthy boundaries, autonomy-supportive parenting, and resolving generational conflict, especially in multicultural and rapidly modernizing societies.